Developing New Software for Functional Food Production - Elena Yu. Titorenko; Natalia B. Trofimova; Evgenia O. Ermolaeva; Ivan E. Trofimov; Leonid I. Breskin; Igor V. Surkov; Natalia V. Astakhova (Техника и технология пищевых производств)
Introduction. Statistical methods of data processing and IT technologies make it possible to introduce new modern methods of hazard and risk analysis in food industry. The research objective was to develop new software that would link together various risk-related production data. Study objects and methods. The research featured food production company LLC Yug (Biysk, Russia) that specializes in functional products and various ready-made software automation solutions. The study also involved statistical methods, methods of observation, collection of primary information, sequential top-down development of algorithms, and the Java programming language. Results and discussion. Food producers have a registration procedure for inconsistencies and violations of permissible limits at critical control points. The authors developed a new software program that allows production line operators to enter data on downtime and other violations of the production process. The program makes it possible for managers to receive up-to-date reports on various criteria, identify violations, and select appropriate corrective actions. This ready-made solution automates the process of accounting and hazard analysis. The program was tested at LLC Yug with the focus on the time that operators and managers needed to register the problem, analyze the data, develop corrective or preventive measures, and apply them. Conclusion. The new software proved to be less time-consuming than standard procedures applied in food industry and made it possible to save the time that operators and managers spent on decision making and reporting.